Estudo cristaloquímico de quatro derivados fenazínicos utilizando a difração de raios-X. - Nunes, Isabelle Karine da Costa (2008)
In general, natural and synthetic phenazines have attracted much attention because of their biological activities, like antitumour agents antimalarials, antibiotics, among others. The natural phenazines are isolated as secondary metabolites of terrestrial and marine microorganisms, mainly of Pseudomonas spp. and Streptomyces spp. This work aiming the structural determination of phenazinics compounds, derivatives that present bioactivity for the treatment of malaria and tuberculosis, using the X-ray diffraction method. The phenazinics compounds had been: (Fena-3244): 14b-Chloro-4amethoxy- 3,3-dimethyl-2,3,4a,14b-tetrahydro-1H-benzo[a]-pyrano[2,3-c]phenazine, (Fena-3243): 1,5-Dioxa-3-dimethyl-benzo[g ]oxanane[e -b]quinoxaline (Fena- 3279): 2,5,5-Trimethyl-benzo[c]-cyclohexan[c ]pyran[e ,a]phenazine (Fena- 3245): 1-allyl2-oxa-10-hydro-2H, 10H-benzo[c]phenazine. All the data collection had been obtained in one automatic KappaCCD, diffractometer using monocromatizada radiation for a graphite crystal, of wave length of 0.71073 Å (molybdenum). The compound Fena-3244 crystallize in the Monoclinic system and belongs to space group P121/n1, with cell parameters a =15.5498 (6) Å, b = 6.97000 (10) Å, c = 17.4872 (7) Å, β = 92.488 (2) Å, with a volume, V = 1893.51 (11) Å3. The compound Fena-3243, crystallize in the Monoclinic system and belongs to the space group P121/C1, with cell parameters of a = 8.3700 (5) Å, b = 11.5120 (9) Å, c = 18.5370 (10) Å, β = 110.223 (4)°, with a volume, V= 1676.03 (19) Å 3. The compound Fena-3279, crystallize in the crystalline system Triclinic, belongs to the space group P - 1, with parameters of a = 10.9810 (4), b = 12.6080 (7), c =16.0080 (6) Å, α = 88.449 (3)°, β = 71.118 (2)°, γ = 87.203 (2)°, V = 1047.18 (8) Å3 . The compound Fena-3245, crystallize in the Triclinic system and belongs to the space group P - 1, with cell parameters of a = 9.4880 (5) Å, b= 17.7650 (13) Å , c= 18.0760 (12) Å , V= 2818.4 (3) Å3 . The results for the compound Fena-3244 and Fena-3243 confirmed their proposed structures for different spectroscopic techniques (NMR, Utraviolet). The results for Fena-3279 show the existing doubts about the aromaticity of ring C. For Fena-3245 revealed the discrepancy structural model of the proposed model as compared to the functional binder group in C5. There were also certain all possible interactions of hydrogen in the bundling of crystalline molecules, allowing them to be established their respective arrangements.